Melatonin reduces glial reactivity in the hippocampus, cortex, and cerebellum of streptozotocin-induced diabetic rats - Baydas, G; Reiter, RJ; Yasar, A; Tuzcu, M; Akdemir, I; Nedzvetskii, VS (Pergamon-Elsevier Science Ltd, 2003)
Hyperglycemia plays a critical role in the development and progression of diabetic neuropathy. One of the mechanisms by which hyperglycemia causes neural degeneration is via the increased oxidative stress that accompanies diabetes. Metabolic and oxidative insults often cause rapid changes in glial cells. Key indicators of this response are increased synthesis of glial fibrillary acidic protein (GFAP) and S100B, both astrocytic markers. In the present study, we examined glial reactivity in hippocampus, cortex, and cerebellum of streptozotocin (STZ)-induced diabetic rats by determining the expression of GFAP and S-100B and we evaluated the effect of melatonin on the glial response. Western blot measurement of contents in brain regions after 6 weeks of STZ-induced diabetes indicated significant increases in these constituents compared with those in nondiabetic controls. Administration of melatonin prevented the upregulation of GFAP in all brain regions of diabetic rats. Using GFAP immunohistochemistry, we observed an increase in GFAP immunostaining in the hippocampus of STZ-diabetic rats relative to levels in the control brains. Treatment with melatonin resulted in an obvious reduction of GFAP-immunoreactive astrocytes in hippocampus. Like GFAP, S100B levels also were increased in all three brain areas of diabetic rats, an effect also reduced by melatonin treatment. Finally, the levels of lipid peroxidation products were elevated as a consequence of diabetes, with this change also being prevented by melatonin. These results suggest that diabetes causes increased glial reactivity possibly clue to elevated oxidative stress, and administration of melatonin represents an achievable adjunct therapy for preventing gliosis. (C) 2003 Elsevier Inc.
Keywords: melatonin; glial fibrillary acidic protein; S100B; lipid peroxidation; diabetes; streptozotocin; hippocampus; cortex; cerebellum; free radicals